EFEKTIVITAS PROGRAM GO LEARNING TERHADAP MOTIVASI BELAJAR MAHASISWA 2021 FKG UNBRAH MASA PANDEMI COVID-19 - Yulia Rahmad; Utmi Arma; Michel Utomo Lauda (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Learning motivation is the driving force of a student that induces and directs learning activities to achieve the student's desired goals. One way to increase learning motivation during the pandemic is through e-learning. The e-learning used in this study is called Go learning. Go Learning is a web-based e-learning program with multiple functions such as assignments, materials, search, and messaging. An Internet connection is required to access the website. The objective of this study was to determine the effectiveness of using the Go Learning program on the motivation of students 2021 class at the Baiturrahmah University, School of Dentistry during the COVID-19 pandemic. Methods: The type of study used is a quantitative pre- experiment with a one-group pre-test and post-test design. The survey was conducted in March-April 2022 with 100 respondents from the overall sample. Data collection was done by providing a questionnaire/Google Form to students of 2021 at Baiturrahmah University, School of Dentistry and interviewing several students. Data analysis was performed using the paired t-test. Result: This study demonstrates the effectiveness of Go-Learning program on motivation to learn with the pre-test value (p = 0.163) and post-test (p = 0.284). Conclusions: The responses received indicate that the use of the Go-Learning program is not effective in motivating students for the 2021 class of Dentistry at the Baiturrahmah University School of Dentistry during the COVID-19 pandemic.